2004
DOI: 10.1007/s00256-004-0841-3
|View full text |Cite
|
Sign up to set email alerts
|

Harris lines of the tibia across centuries: a comparison of two populations, medieval and contemporary in Central Europe

Abstract: Objective: To determine the incidence of Harris lines in two medieval populations which inhabited the Canton of Berne, in Central Switzerland, and to compare the results with those of a contemporary population living in the same geographical area. A simplified method is described for measuring the age of the individual at the time of formation of Harris lines, with possible future applications. Design and patients: Radiographs of 112 wellpreserved tibiae of skeletons of two medieval populations from the eighth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 15 publications
3
21
0
Order By: Relevance
“…An analysis of archaeological and anthropological characteristics (Papageorgopoulou, 2008) has shown no evidence of socioeconomic differences in terms of gravegoods, place of interment, and type of burial among the individuals with and without HLs. Comparable results regarding the frequency of HLs in skeletal material of similar geographical and chronological settings were found in skeletal material from Switzerland (13th214th c. AD) (Ameen et al, 2005), from medieval (10th-14th c AD) Poland (Gronkiewicz et al, 2001;Nowak and Piontek, 2002;Piontek et al, 2001) from medieval and early modern (5th-19th c. AD) Southern Germany (Haidle, 1997) and from North The relationship between age (in years) and tibia length (in mm) at Tomils (11th-15th c.AD) [F1 after Martin (1928)]. The symbols indicate the relative frequency of HLs per year: 2 few HLs (< 0.27), * normal frequency of HLs (IQR: 0.27-1.00), 1 many HLs (>1.00).…”
Section: Discussionsupporting
confidence: 77%
“…An analysis of archaeological and anthropological characteristics (Papageorgopoulou, 2008) has shown no evidence of socioeconomic differences in terms of gravegoods, place of interment, and type of burial among the individuals with and without HLs. Comparable results regarding the frequency of HLs in skeletal material of similar geographical and chronological settings were found in skeletal material from Switzerland (13th214th c. AD) (Ameen et al, 2005), from medieval (10th-14th c AD) Poland (Gronkiewicz et al, 2001;Nowak and Piontek, 2002;Piontek et al, 2001) from medieval and early modern (5th-19th c. AD) Southern Germany (Haidle, 1997) and from North The relationship between age (in years) and tibia length (in mm) at Tomils (11th-15th c.AD) [F1 after Martin (1928)]. The symbols indicate the relative frequency of HLs per year: 2 few HLs (< 0.27), * normal frequency of HLs (IQR: 0.27-1.00), 1 many HLs (>1.00).…”
Section: Discussionsupporting
confidence: 77%
“…Harris lines are radiodense lines perpendicular to the longitudinal axis of long bones (Jopp et al, 2006). They can be found in 20% of the bones of the contemporary population, but are much more common (80-100%) in the bones of archaeological remains (Hughes et al, 1996;Ameen et al, 2005). They result from temporary slowing or cessation of longitudinal growth in periods of childhood stress, infection, trauma or dietary restriction and subsequent recovery (Park and Richter, 1953).…”
Section: Resultsmentioning
confidence: 97%
“…Rickets due to child abuse and child neglect is unfortunately also present in our societies [6,7,16,160,161,162,163,164,165,166]. Child neglect rarely receives attention, usually only when traces of physical ill-treatment can be observed [162,164].…”
Section: Public Health and Socio-ideological Debatementioning
confidence: 99%
“…Large population surveys, such as the Nutrition Examination Survey and National Health, have suggested that many children and pregnant women may be affected by Vitamin D deficiency at some point during their lifetime [8,9,10,11,12,13]. Change of habits, such as less sunlight exposure, indoor living, dietary choices, and increasing rates of dietary allergy, are likely playing a significant role in the increase of this rate in some segments of the worldwide population according to the most recent evaluation of public health indicators [11,14,15,16,17,18,19,20,21,22]. …”
Section: Introductionmentioning
confidence: 99%